Seismic evaluation of Site-City interaction effects between city blocks - Vicencio, Felipe; Alexander, Nicholas A. (Frontiers in Built Environment, 2024)
In urban environments, buildings are often seismically designed with their standalone response, such as isolated structures devoid of surrounding structures. Nonetheless, there is always a chance that a significant seismic interaction between nearby buildings through the underlying soil will occur in big urban areas with high building densities. This paper evaluates the Site-City interaction (SCI) between different city block arrangements under seismic excitation given different parameters of the buildings and centre-to-centre interbuilding distances. A database of strong ground motion records with Far-Field, Near-Field Without Pulse and Near-Field Pulse-Like characteristics are employed. The results suggest that the SCI effects were strongly influenced by the building properties and resonance effects of the soil stratum. Furthermore, as a mean for all the earthquakes considered here, the SCI can amplify or reduce the seismic response of the buildings, depending on the relative position between the city blocks. and spatial distribution of buildings, the dynamic properties of the structures and the soil, and the natural characteristics of the earthquakes. So, different approach to analyze this complex problem.The ability to perform complex analyses that account for intricate geometric arrangements, nonlinearities, and the radiating damping of soil has been made possible by the rapid advancement in computational power and the use of numerical methods. Numerical methods such as Finite Element method (FEM) (